2015
DOI: 10.3389/fmicb.2015.00209
|View full text |Cite
|
Sign up to set email alerts
|

Diel metabolomics analysis of a hot spring chlorophototrophic microbial mat leads to new hypotheses of community member metabolisms

Abstract: Dynamic environmental factors such as light, nutrients, salt, and temperature continuously affect chlorophototrophic microbial mats, requiring adaptive and acclimative responses to stabilize composition and function. Quantitative metabolomics analysis can provide insights into metabolite dynamics for understanding community response to such changing environmental conditions. In this study, we quantified volatile organic acids, polar metabolites (amino acids, glycolytic and citric acid cycle intermediates, nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
86
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 47 publications
3
86
0
Order By: Relevance
“…High levels of nitrogenase gene expression (16,29,30) and N 2 fixation activity (30) have been observed at sunset in the Octopus Spring and Mushroom Spring mats. While we cannot rule out the possibility that all H 2 production in the afternoon-evening transmission was due to nitrogenase activity, the massive accumulation of fermentation products shown in dark-incubated mats from Mushroom Spring (19,22) and the very low nighttime pH values measured in this study provide evidence that fermentation might be another source of H 2 accumulation in the mat. Previously measured accumulations of acetate plus propionate in dark-incubated vials containing a 1-cm-deep core of the mat (22) thus indicate that volatile fatty acids may build up to tens of millimolar concentrations in the upper millimeters of the mat during the night.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…High levels of nitrogenase gene expression (16,29,30) and N 2 fixation activity (30) have been observed at sunset in the Octopus Spring and Mushroom Spring mats. While we cannot rule out the possibility that all H 2 production in the afternoon-evening transmission was due to nitrogenase activity, the massive accumulation of fermentation products shown in dark-incubated mats from Mushroom Spring (19,22) and the very low nighttime pH values measured in this study provide evidence that fermentation might be another source of H 2 accumulation in the mat. Previously measured accumulations of acetate plus propionate in dark-incubated vials containing a 1-cm-deep core of the mat (22) thus indicate that volatile fatty acids may build up to tens of millimolar concentrations in the upper millimeters of the mat during the night.…”
Section: Discussionmentioning
confidence: 85%
“…Earlier studies have also reported H 2 formation in hot spring microbial mats, where H 2 production may be due to fermentation (18,19,22,36) or to formation as a by-product of nitrogenase activity during N 2 fixation (30). The relative importance of these processes for H 2 dynamics in hot spring cyanobacterial communities has remained unclear, while studies of hypersaline and coastal cyanobacterial mats have identified fermentation as the major H 2 source (7-9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A combined approach of these methods, indeed, was recently used to identify two novel candidate phyla, Calescamantes and Candidatus kryptonia, by the analysis of different SAGs and metagenomic databases collected in different high-temperature environments (Eloe-Fadrosh et al 2016;Kim et al 2015) proving that, although metagenomics and single-cell genomics are informative of their own, the results of the mixed approach could be greater than the sum of their parts.…”
Section: Nr Low Dissolved Oxygen Concentrationmentioning
confidence: 99%